Analisis Pengalaman Pengguna Aplikasi Gojek dan Grab dengan Pendekatan User Experience Questionnaire - Diana Khuntari (Maranatha University Press, 2022)
Technological developments have an impact on the presence of Super Apps, such as: Gojek and Grab. The presence of these two applications has an effect on the lifestyle in society which is increasingly facilitated by various services that are presented in only one application. The Gojek and Grab applications have many similarities, including in terms of their use. These two applications are very popular and favored by the community because they are practical and help various community activities, for example: food ordering services, delivery of goods, transportation, and non-cash payments. This study was conducted to determine whether there are differences in user experience with the application with case studies in people living in Yogyakarta. User experience measurement is carried out using the User Experience Questionnaire (UEQ) approach on attractive, perspicuity, efficiency, dependability, stimulation, and novelty variables. This study uses a comparative descriptive method with a quantitative approach. The results showed that all Gojek and Grab application user experience variables got positive values ??and there were no significant differences in all variables. However, based on the UEQ measurement, it is known that the Gojek application is superior to the Grab application in perspicuity and novelty variables. Meanwhile, the Grab application is superior to the Gojek application in terms of efficiency, dependability, and stimulation variables. To improve the user experience for the Gojek and Grab applications, it is necessary to improve the quality of the perspicuity and dependability variables.